The Effectiveness of Red Ginger Extract (Zingiber Officinale Var. Rubrum) on Decreased Blood Glucose Levels in Mice (Mus Musculus) - Nur khafyah; Sisilia TR Dewi; Jumain Jumain (Indonesian Health Journal, 2023)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia conditions (increased blood glucose) caused by abnormalities in insulin secretion, abnormalities in the action of insulin or perhaps both. Red Ginger (Zingiber officinale var. rubrum) contains alkaloids, flavanoids, tannins, saponins, gingerol and shagol which have blood glucose-lowering, anti-inflammatory, anticancer and antitumor effects. This study aims to determine the effectiveness of Red Ginger extract against decreasing blood glucose levels in mice (Mus musculus). This research is a type of experimental study conducted to determine the effectiveness of red ginger extract against decreasing blood glucose levels in mice. This study was conducted using alloxane as a diabetes inducer, Na CMC 1% as a negative control, glibenclamide as a positive control, extract dose 2 %, 5 % and 7 % orally for 7 days in 5 groups of test animals. The results of the study obtained 1% Na-CMC results showed a percentage decrease, namely -16.32% and -103.03%. In the group of mice given Red Ginger extract 2% showed a percentage decrease, namely 105.57% and 102.04%. The group of mice given Red Ginger extract 5% showed a percentage decrease of 105.83% and 86.84%. The group of mice given 7% Red Ginger extract showed a percentage decrease, namely 67.34% and 97.45%. The group of mice suspended by glibenclamide showed a percentage decrease of 73.05% and 66.66%. It can be concluded that the administration of Red Ginger extract has been shown to reduce blood glucose levels in aloxane-induced mice at concentrations of 2%,5% and 7% with significant values (p < 0.05) indicating a difference and obtained the most effective concentration in lowering blood glucose levels in mice (Mus musculus) is a concentration of 7%.